2014
DOI: 10.1371/journal.pgen.1004309
|View full text |Cite
|
Sign up to set email alerts
|

p53 Requires the Stress Sensor USF1 to Direct Appropriate Cell Fate Decision

Abstract: Genomic instability is a major hallmark of cancer. To maintain genomic integrity, cells are equipped with dedicated sensors to monitor DNA repair or to force damaged cells into death programs. The tumor suppressor p53 is central in this process. Here, we report that the ubiquitous transcription factor Upstream Stimulatory factor 1 (USF1) coordinates p53 function in making proper cell fate decisions. USF1 stabilizes the p53 protein and promotes a transient cell cycle arrest, in the presence of DNA damage. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 72 publications
(93 reference statements)
1
39
0
Order By: Relevance
“…Nonetheless, under stress conditions such as DNA damage, oxidative stress, hypoxia and oncogene expression, USF1 impedes MDM2‐mediated p53 degradation, which enhances the stability of p53 and facilitates cell cycle arrest, DNA repair or apoptosis (Fig. ) . Hence, the implication of USF1 in p53 pathway suggested that USF1 may have other functions independent of the well‐established role as a transcriptional factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, under stress conditions such as DNA damage, oxidative stress, hypoxia and oncogene expression, USF1 impedes MDM2‐mediated p53 degradation, which enhances the stability of p53 and facilitates cell cycle arrest, DNA repair or apoptosis (Fig. ) . Hence, the implication of USF1 in p53 pathway suggested that USF1 may have other functions independent of the well‐established role as a transcriptional factor.…”
Section: Discussionmentioning
confidence: 99%
“…2). 39 Hence, the implication of USF1 in p53 pathway suggested that USF1 may have other functions independent of the well-established role as a transcriptional factor. Alternatively, USF1 suppresses the expression of human telomerase reverse transcriptase (hTERT) in oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that USF1 is equally as efficient as Nutlin-3a treatment and superior to other transcription factors such ATF3 and TFII31 in p53 stabilization during genotoxic stress. 34 Taken together, these findings indicate that ubiquitylationdependent pathways ensure minimal levels of p53 in normal cells whereas inhibition of these factors by messengers of DNA damage induces p53 to protect cells from transformation-inducing alterations.…”
Section: Auditing P53 Levels: Regulation By Degradationmentioning
confidence: 75%
“…Therefore, we undertook analysis of the Angptl2 promoter using the UCSC genome browser and observed binding motifs for many transcription factors that may potentially regulate Angptl2 . Among them is USF1, a transcription factor induced by UV‐B, as well as the cAMP response element binding protein (CREB) . We conclude that CE extracts may inhibit ANGPTL2 by intefering with USF1 transcriptional activity, a mechanism we will explore in future studies.…”
Section: Discussionmentioning
confidence: 99%